Management of Cystoid Macular Edema in Retinitis Pigmentosa: A Systematic Review and Meta-Analysis - Chen, Chen; Liu, Xia; Peng, Xiaoyan (Frontiers in Medicine, 2022)
Background To date, various treatments for cystoid macular edema (CME) in retinitis pigmentosa (RP) have been reported. We performed a systematic review and meta-analysis to evaluate the efficacy and safety of current treatments for RP-CME. Methods PubMed, Embase and the Cochrane library were searched from inception to August 2021. ClinicalTrials.gov, WHO ICTRP and ISRCTN were also searched for relevant studies. Only studies published in English were included. The RoB 2 tool was used to evaluate the risk of bias of randomized controlled trials (RCTs), and the MINORS scale was used to assess the methodological quality of non-RCTs. Review manager (Revman) was used to pool the data. The primary outcomes included the change of central macular thickness (CMT) and best-corrected visual acuity (BCVA) from baseline. The secondary outcomes included fluorescein angiography (FA) leakage, rebound of CME and adverse effects. Results Thirty-two studies were included in the current systematic review and 7 studies were used for meta-analysis. Treatments for RP-CME included oral and topical carbonic anhydrase inhibitors (CAIs), systematic and local steroids, anti-VEGF therapy, NSAIDS, grid LASER photocoagulation, subliminal micropulse LASER, vitrectomy, lutein supplement and oral minocycline. CAIs and local steroids were proved to be effective in reducing CMT. The effects of anti-VEGF reagents varied among studies. Regarding other treatments, only one study for each method fitted the inclusion criteria, so the evidence was very limited. Conclusion Topical CAIs, oral CAIs and local steroids are effective in treating RP-CME. However, due to the overall inferior design and small patient number of the included studies, the quality of evidence was poor. Systematic steroids, LASER, NSAIDS and vitrectomy may also be effective, nevertheless, considering the limited number of studies, no conclusion could be drawn regarding these treatments. More well-designed and conducted studies are needed in this field. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021273979, identifier CRD42021273979.